MORPHOLOGICAL CHARACTERISTICS OF NEPENTHES IN PEAT SWAMP AREA OF TULUNG SELAPAN, SOUTH SUMATERA - Wardana, Singgih Tri; Ilmawati, Ika; Tanzerina, Nina; Juswardi, Juswardi; Aminasih, Nita; Harmida, Harmida (BIOVALENTIA: Biological Research Journal, 2019)
This study is aimed to recognise the morphological characteristics of Nepenthes mirabilis and Nepenthes gracilis in peat swamp area including stem, leaf, tendril, pitcher, flower, fruit, and seed.  This study has been conducted in January  until April 2018, located in Petaling Village Tulung Selapan Sub-District, Ogan Komering Ilir, South Sumatera. This study uses an exploratory method and the the observation sample using the method of random plot is chosen by purposive sampling. Parameters observed morphological characteristics of Nepenthes include stems, leaves, tendrils, pitcher, flower, adn fruit, as well as measurement of environmental factors. Based on the study, the researcher obtained two types of Nepenthes which are Nepenthes mirabilis and Nepenthes gracilis in  peat swamp area of Petaling Village Tulung Selapan Sub-District, Ogan Komering Ilir. Nepenthes mirabilis has a teres stem, leaves that in the form of oblong to lanceolate, has a petiolate, the edge of the leaves is flat covered by smoothy hair, thick peristome in size of 0,4-0,5 cm. Meanwhile stem Nepenthes gracilis has triangular stem, leaves in formed of lanceolate, sessile, flat edge of leaves, thin peristome in size of 0,1-0,2 cm. The pitcher shape of Nepenthes mirabilis and Nepenthes gracilis are cylindrical, infundibulate, and waist. The flower of Nepenthes mirabilis and Nepenthes gracilis are compound in type of  raceme inflorescences. The fruit is formed as capsula, has four lobed, and contains numerous seeds. The seed is spindle-like and white colored.